2000
DOI: 10.1159/000054517
|View full text |Cite
|
Sign up to set email alerts
|

Galanin Immunoreactivity in Mouse Basal Forebrain: Sex Differences and Discrete Projections of Galanin-Containing Cells beyond the Blood-Brain Barrier

Abstract: The distribution of galanin-immunoreactive (GAL-IR) cell bodies in the basal forebrain of mice was investigated. The overall pattern of staining for GAL in the area of brain analyzed was similar to that reported in other species with noticeable variations. Distinctive groups of GAL-IR cells were present in the bed nucleus of stria terminalis (BNST), supraoptic nucleus, retrochiasmatic supraoptic nucleus (SOR), magnocellular paraventricular nucleus, arcuate nucleus (ARC) and the nucleus circularis which is one … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
11
1

Year Published

2001
2001
2012
2012

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 38 publications
5
11
1
Order By: Relevance
“…of galanin mRNA expression in the hypothalamus of the mouse are in good agreement with a recent report of galanin immunoreactivity in the murine basal forebrain, 32 although the relative abundance of galanin peptide reported is at slight variance with our mRNA ®ndings in various regions. It is conceivable that this variance results from methodological differences between the two studies; alternatively, it is possible that it simply re¯ects the fact that levels of mRNA and peptide are regulated differentially in some brain regions, as has been reported in the hypothalamus for cells that are actively secreting peptides.…”
Section: Comparative Distribution and Intensity Of Galanin Expressionsupporting
confidence: 93%
“…of galanin mRNA expression in the hypothalamus of the mouse are in good agreement with a recent report of galanin immunoreactivity in the murine basal forebrain, 32 although the relative abundance of galanin peptide reported is at slight variance with our mRNA ®ndings in various regions. It is conceivable that this variance results from methodological differences between the two studies; alternatively, it is possible that it simply re¯ects the fact that levels of mRNA and peptide are regulated differentially in some brain regions, as has been reported in the hypothalamus for cells that are actively secreting peptides.…”
Section: Comparative Distribution and Intensity Of Galanin Expressionsupporting
confidence: 93%
“…36,37 While some studies have reported no sex difference in galanin, 38 others have reported a relatively small sex difference in galanin in both rats 36 and mice. 39 In the present study, two-week-old males expressed more galanin mRNA than females in the amygdala; however, there was no sex difference detected in the number of galaninir cells in either the CMA or the BST in adulthood. Galanin is regulated by circulating testosterone levels, 40 and the adult animals in this study received testosterone-filled implants, whereas, the two-week-old animals did not.…”
Section: Discussioncontrasting
confidence: 62%
“…It is of interest that each NPY receptor mutant also leads to a sexually dimorphic phenotype, as was the case with the GAL Ϫ/Ϫ and GAL Ϫ/Ϫ /NPY Ϫ/Ϫ mutants in the present study. This may not be unexpected, considering that the expression of both galanin and NPY is sexually dimorphic in brain regions involved in energy homeostasis, such as the arcuate nucleus (38,53).…”
Section: Vol 24 2004 Endocrine Deficits In Npy/galanin Knockout Micmentioning
confidence: 99%